Detection and characterization of E. coli O157:H7 and induced shiga toxin-2 coding bacteriophages - Ehlers, M.M. (Marthie Magdaleen) (University of Pretoria, 2013)
Dissertation (MSc (Medical Virology))--University of Pretoria, 2005.